The Pengaruh Store Atmosphere, Mood, dan Lifestyle Terhadap Keputusan Pembelian ( Studi Kasus Konsumen Cafe Legend Coffee Yogyakarta ): Pengaruh Store Atmosphere, Mood, dan Lifestyle Terhadap Keputusan Pembelian ( Studi Kasus Konsumen Cafe Legend Coffee Yogyakarta ) - Siti Mastinah Siti (Politeknik Kutaraja, 2021)
This study aims to determine the effect of Store Atmosphere, Mood, and Lifestyle partially on consumer purchasing decisions of Cafe legend Coffee in Yogyakarta. This research is a survey research using a questionnaire as the instrument. The population used in this study are consumers of Cafe legend Coffee Yogyakarta who have made purchases at Cafe legend Coffee Jl. Abu Bakar Ali No 24-26, kridosono, Kotabaru, Kec. Gondokusuman, City of Yogyakarta. Samples were taken as many as 80 respondents using purposive sampling method, namely the determination of respondents from the population with predetermined criteria. The validity test of the instrument used Pearson Correlation, while the reliability test used Alpha Cronbach. The analysis technique used is multiple regression analysis. The results of the study found that: (1) Store atmosphere has a positive effect on consumer purchasing decisions with a value of t count> t table, 2.166> 1.992 with a significance of 0.033 <0.05. (2) Mood has a positive effect on consumer purchasing decisions with a value of t count> t table, 3.761> 1.992 with a significance of 0.000 <0.05. And (3) Lifestyle has a positive effect on consumer purchasing decisions with a value of t count> t table, 2.464> 1.992 with a significance of 0.016 <0.05. (5) The magnitude of the influence of Store Atmosphere, Mood, and Lifestyle on consumer purchasing decisions (adjusted R2) is 71.9%. The regression equation obtained is Y = 0.791 + 0.069X1 + 0.591X2 + 0.120X3 + e.